Postabortion care availability, readiness, and accessibility in Niger in 2022: results from linked facility-female cross-sectional data - Haley L. Thomas; Souleymane Alzouma; Sani Oumarou; Caroline Moreau; Suzanne O. Bell (BMC, 2023)
Abstract Background Postabortion care (PAC), which is an essential element of emergency obstetric care, is underresearched in Niger. The study aims to assess the availability, readiness, and accessibility of facility-based PAC services in Niger. Methods This study uses female and facility data from Performance Monitoring for Action Niger. The female data include a nationally representative sample of women aged 15-49 (n = 3,696). Using GPS coordinates, these female data were linked to a sample of public and private facilities (n = 258) that are expected to provide PAC. We assessed PAC availability and facility readiness to provide basic and comprehensive PAC using the signal functions framework, overall and by facility type. We then calculated the distance between women and their closest facility and estimated the proportion of women living within five kilometers (5 km) of a facility providing any PAC, basic PAC, and comprehensive PAC, overall and by women's background characteristics. Results Only 36.4% and 14% of eligible facilities had all basic and comprehensive PAC signal functions, respectively. Oxytocics and laparotomy were the most missing signal function for basic and comprehensive PAC, respectively. Private facilities were the least ready to provide the full range of PAC services. While 47% of women lived within 5 km of a facility providing any PAC services, only 33.4% and 7.9% lived within 5 km of a facility providing all basic and all comprehensive PAC signal functions, respectively. Women who were divorced/widowed, had higher levels of education, and were living in urban areas had increased odds of living within 5 km of a facility with any or basic PAC. Women who were never married had increased odds of living within 5 km of a facility with comprehensive PAC, while urban residence was fully predictive of living within 5 km of a facility with comprehensive PAC. Conclusions This study found PAC availability and readiness to be insufficient in Niger, with inadequate and disparate accessibility to facilities providing PAC services. We recommended stakeholders ensure stock of essential commodities and availability of PAC services at primary facilities in order to mitigate the negative maternal health repercussions of unsafe abortion in this setting.